Double Renal Artery in Cerdocyon thous - Shirley Viana Peçanha; Raquel Batista Junger de Carvalho; Carlos Augusto dos Santos-Sousa; Emanoelli Aparecida Rodrigues dos Santos; Paulo Souza-Junior; Marcelo Abidu-Figueiredo (Revista MVZ Cordoba, 2020)
Objective. The aim of this study was explored the duplicity of renal artery in a specimen of Cerdocyon thous, focusing on the possibilities of clinical-surgical implication of this anatomical variation. Materials and methods. Were dissected 32 specimens of Cerdocyon thous, obtaine from the collections of the Laboratório de Ensino e Pesquisa em Morfologia dos Animais Domésticos e Selvagens do Departamento de Anatomia Animal e Humana, da Universidade Federal Rural do Rio de Janeiro e Laboratório de Anatomia Animal da Universidade Federal do Pampa. Results. Were observed a numerical variation in the left renal artery in an adult female cadaver. The left kidney had two renal arteries, one cranial and another caudal. The first renal artery of the left kidney, measuring 2.25 cm in length, originated laterally from the abdominal aorta at the level of the third lumbar vertebra. Moreover, it emanated two pre-hilar branches, one dorsal and one ventral, with the ventral branch supplying also to the adrenal gland. The second renal artery also originated laterally from the abdominal aorta at the level of the third lumbar vertebra and measured 2.36 cm in length. It also emitted two pre-hilar branches, one cranial and another caudal, which emitted the ureteral branch. Conclusions. Numerical variations of the renal arteries should be considered in the execution of surgical, radiological and experimental procedures in order to avoid mistakes made due to lack of knowledge of the possibility these variations both in domestic and wild animals.